Pengoptimalan Jumlah Man Power dengan Metode Work Force Analysis - Christian Wibisono; I Nyoman Sutapa (Jurnal Titra, 2017)
The purpose of this study is to minimize man power cost. The main problem of this company is that ineffective time by workers at delivery area is very big. It happens because supervisor does not count the time that workers need to do their job yet. The improvements for this problem are giving total number of man power according the standard time and making a preparation schedule so every shift has a balance workload.